2018
DOI: 10.1177/1350508418777891
|View full text |Cite
|
Sign up to set email alerts
|

Emancipation through digital entrepreneurship? A critical realist analysis

Abstract: Digital entrepreneurship is presented in popular discourse as a means to empowerment and greater economic participation for under-resourced and socially marginalised people. However, this emancipatory rhetoric relies on a flat ontology that does not sufficiently consider the enabling conditions needed for successful digital enterprise activity. To empirically illustrate this argument, we examine three paired cases of UK women digital entrepreneurs, operating in similar sectors but occupying contrasting social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 104 publications
2
89
0
Order By: Relevance
“…A similar approach is also presented in the study by A. Pergelova et al, where it is shown that digital technologies contribute to the development of traditional entrepreneurship of women [5], B. Hansen on the use of digital technologies by Chinese entrepreneurs [6]. Often digital technologies are considered as a way to involve marginal groups or people with disabilities in entrepreneurship [7].…”
Section: Introductionmentioning
confidence: 88%
“…A similar approach is also presented in the study by A. Pergelova et al, where it is shown that digital technologies contribute to the development of traditional entrepreneurship of women [5], B. Hansen on the use of digital technologies by Chinese entrepreneurs [6]. Often digital technologies are considered as a way to involve marginal groups or people with disabilities in entrepreneurship [7].…”
Section: Introductionmentioning
confidence: 88%
“…An analysis of the initial nodes suggests that the dimension Entrepreneur relates primarily to the digital behavior patterns, social impact, and knowledge nodes. The variety of categories covers the range from digital entrepreneurial intentions to start a business [63] and the related decision-making process [62,64] to knowledge integration [66] and social outcomes for entrepreneurs [58][59][60][61].…”
Section: Entrepreneurmentioning
confidence: 99%
“…In doing so, social media is changing how "organizations do business" (Arnaboldi & Coget, 2016, p. 47). In turn, and despite critical voices about the expected benefits for entrepreneurs (Martinez Dy, Martin, & Marlow, 2018), it becomes unthinkable not to be on social media (cf. Duffy & Hund, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the way in which entrepreneurs use social media and what that means for the processes and practices of entrepreneurial development and their outcomes is underreasearched and under-theorised (Achtenhagen, 2017;Giones & Brem, 2017;Horst & Murschetz, 2019;Kraus et al, 2019;Martinez Dy et al, 2018;Nambisan, 2018;Shen et al, 2018). This is evident in recent calls to bring mainstream entrepreurship and predominantly industry-focused research on media entrepreneurship closer together to advance theorybuilding (Achtenhagen, 2017) and, in turn, create new theoretical constructs that enable capturing and investigating interdisciplinary topics (Horst & Murschetz, 2019).…”
Section: Introductionmentioning
confidence: 99%